1983
DOI: 10.1152/jn.1983.50.6.1446
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of spinal nociceptive information by stimulation in midbrain of the cat is blocked by lidocaine microinjected in nucleus raphe magnus and medullary reticular formation

Abstract: The organization in the brain stem of descending inhibitory control of spinal nociceptive information was studied in anesthetized, paralyzed cats by quantitatively evaluating the effects of reversible blocks produced by lidocaine microinjected in the medial and/or lateral medulla. Spinal neuronal inhibition produced by stimulation in the nucleus raphe magnus (NRMS) was compared to the inhibition of the same dorsal horn neurons produced by stimulation 2 mm lateral in the medullary reticular formation (MRFS). Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(40 citation statements)
references
References 8 publications
3
37
0
Order By: Relevance
“…Lesions of A5 reduce the antinociceptive effect of microinjecting the non-selective adrenergic antagonist phentolamine into the RVM (Proudfit, 1988) suggesting that this A5-derived NE input to RVM is involved in pain modulation. The antinociceptive effect of stimulating in the dorsolateral pontomesencephalic region, near A7, is reduced by reversible inactivation of the RVM (Gebhart et al, 1983). Although that study did not directly implicate the noradrenergic A7 neurons, its results plus the demonstrated projection of A5 and A7 neurons to both the RVM and the dorsal horn (Reichling et al, 1988;Kwiat and Basbaum, 1992) are consistent with a role for A7 projections to RVM in pain modulation.…”
Section: Source Of Th Profiles In the Rvmmentioning
confidence: 62%
“…Lesions of A5 reduce the antinociceptive effect of microinjecting the non-selective adrenergic antagonist phentolamine into the RVM (Proudfit, 1988) suggesting that this A5-derived NE input to RVM is involved in pain modulation. The antinociceptive effect of stimulating in the dorsolateral pontomesencephalic region, near A7, is reduced by reversible inactivation of the RVM (Gebhart et al, 1983). Although that study did not directly implicate the noradrenergic A7 neurons, its results plus the demonstrated projection of A5 and A7 neurons to both the RVM and the dorsal horn (Reichling et al, 1988;Kwiat and Basbaum, 1992) are consistent with a role for A7 projections to RVM in pain modulation.…”
Section: Source Of Th Profiles In the Rvmmentioning
confidence: 62%
“…Such antinociception is thought to result in inhibition of nociceptive neurons in the dorsal horn (Liebeskind et al, 1973), directly and via the nucleus raphe magnus of the rostral ventromedial medulla (Gebhart et al, 1983). Thus, the periaqueductal gray modulates the amount of nociceptive information which is transmitted to higher brain centres, and hence, affects the magnitude of pain experienced.…”
Section: Supraspinal Modulation Of Pain-mentioning
confidence: 99%
“…These results may indicate a role of MRF neurons in visceral nociception as well. It has been shown that the MRF can modulate nociceptive processing by its descending (excitatory and inhibitory) inputs (McCreery et al 1979;Haber et al 1980;Gebhart et al 1983;Zhuo & Gebhart, 1990, 2002a, and work as relay nuclei to higher centres for nociceptive processing and ultimately pain perception (Foreman et al 1984).…”
Section: Convergence Of Ub and Colon Inputs In The Mrfmentioning
confidence: 99%